In vitro anti-oxidant potential of new metabolites from Hypericum oblongifolium (Guttiferae) - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Imran Ali (Natural Product Research, 2015)

Chemical characterisation of bioactive compounds in Medicago sativa growing in the desert of Oman - Muhammad Asif Hanif; Ahmed Yahya Al-Maskari; Jamal Nasser Al-Sabahi; Ibtisam Al-Hdhrami; Muhammad Mumtaz Khan; Ahlam Al-Azkawi; Abdullah Ijaz Hussain (Natural Product Research, 2015)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Three-Dimensional Stochastic Characterization of Shale SEM Images - Pejman Tahmasebi; Farzam Javadpour; Muhammad Sahimi (Transport in Porous Media, 2015)

Oral tissue engineering progress and challenges - Muhammad Sohail Zafar; Zohaib Khurshid; Khalid Almas (Tissue Engineering and Regenerative Medicine, 2015)

RETRACTED ARTICLE: Support vector regression methodology for prediction of output energy in rice production - Marziye Yousefi; Benyamin Khoshnevisan; Shahaboddin Shamshirband; Shervin Motamedi; Mohd Hairul Nizam Md. Nasir; Muhammad Arif; Rodina Ahmad (Stochastic Environmental Research and Risk Assessment, 2015)

Comparative Assessment of Synthetic-derived and Conventional Bread Wheat Advanced Lines Under Osmotic Stress and Implications for Molecular Analysis - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Awais Rasheed; Hassan Sher; Alvina Gul Kazi; Abdul Mujeeb-Kazi (Plant Molecular Biology Reporter, 2015)

Le4 Is an Epicotyl Preferential Homologue of the Soybean Seed-Specific Le1 Lectin and the Vegetative Le3 Lectin Genes - Muhammad Chragh; Yevgen Zolotarov; Hanaa Saeed; Martina V. Strömvik (Plant Molecular Biology Reporter, 2015)

Diazoxide preconditioning of endothelial progenitor cells from streptozotocin-induced type 1 diabetic rats improves their ability to repair diabetic cardiomyopathy - Muhammad Ali; Azra Mehmood; Muhammad Sohail Anjum; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Molecular and Cellular Biochemistry, 2015)

Mutualistic fungal endophytes produce phytohormones and organic acids that promote japonica rice plant growth under prolonged heat stress - Muhammad Waqas; Abdul Latif Khan; Raheem Shahzad; Ihsan Ullah; Abdur Rahim Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2015)

Interleukin-27 and IFNγ regulate the expression of CXCL9, CXCL10, and CXCL11 in hepatitis - Laëtitia Basset; Sylvie Chevalier; Yannic Danger; Muhammad Imran Arshad; Claire Piquet-Pellorce; Hugues Gascan; Michel Samson (Journal of Molecular Medicine, 2015)

Study of physio-psychological effects on traffic wardens due to traffic noise pollution; exposure-effect relation - Shamas Tabraiz; Saeed Ahmad; Iffat Shehzadi; Muhammad Bilal Asif (Journal of Environmental Health Science and Engineering, 2015)

Genetics, realized heritability and preliminary mechanism of spinosad resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae): an invasive pest from Pakistan - Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad; Naeem Abbas (Genetica, 2015)

Decomposing the trade-environment nexus for Malaysia: what do the technique, scale, composition, and comparative advantage effect indicate? - Chong Hui Ling; Khalid Ahmed; Rusnah Binti Muhamad; Muhammad Shahbaz (Environmental Science and Pollution Research, 2015)

Dolomite application to acidic soils: a promising option for mitigating N2O emissions - Muhammad Shaaban; Qi-an Peng; Ronggui Hu; Yupeng Wu; Shan Lin; Jinsong Zhao (Environmental Science and Pollution Research, 2015)

Causal nexus between energy consumption and carbon dioxide emission for Malaysia using maximum entropy bootstrap approach - Sehrish Gul; Xiang Zou; Che Hashim Hassan; Muhammad Azam; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Co-occurrence of arsenic and fluoride in the groundwater of Punjab, Pakistan: source discrimination and health risk assessment - Atta Rasool; Tangfu Xiao; Zenab Tariq Baig; Sajid Masood; Khan M. G. Mostofa; Muhammad Iqbal (Environmental Science and Pollution Research, 2015)

Adoption and intensity of integrated pest management (IPM) vegetable farming in Bangladesh: an approach to sustainable agricultural development - Muhammad Humayun Kabir; Ruslan Rainis (Environment, Development and Sustainability, 2015)

Effect of ethylene glycol dimethacrylate on swelling and on metformin hydrochloride release behavior of chemically crosslinked pH–sensitive acrylic acid–polyvinyl alcohol hydrogel - Muhammad Faheem Akhtar; Nazar Muhammad Ranjha; Muhammad Hanif (DARU Journal of Pharmaceutical Sciences, 2015)

Molecular docking and inhibition studies on the interactions of Bacopa monnieri’s potent phytochemicals against pathogenic Staphylococcus aureus - Talha Bin Emran; Md Atiar Rahman; Mir Muhammad Nasir Uddin; Raju Dash; Md Firoz Hossen; Mohammad Mohiuddin; Md Rashadul Alam (DARU Journal of Pharmaceutical Sciences, 2015)

Development of MY-DRG casemix pharmacy service weights in UKM Medical Centre in Malaysia - Saad Ahmed Ali Jadoo; Syed Mohamed Aljunid; Amrizal Muhammad Nur; Zafar Ahmed; Dexter Van Dort (DARU Journal of Pharmaceutical Sciences, 2015)

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers - Sadaf S. Arain; Tasneem G. Kazi; Hassan I. Afridi; Farah N. Talpur; Atif G. Kazi; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Muhammad A. Kamboh (Biological Trace Element Research, 2015)

New fossil remains of family Cervidae from the Dhok Pathan Formation (Middle Siwaliks) of Pakistan - Abdul Ghaffar; Muhammad Akhtar; Muhammad Akbar Khan; Muhammad Khaled Siddiq (Geosciences Journal, 2015)

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes - Naila Shahid; Sana Tahir; Abdul Q. Rao; Sameera Hassan; Anwar Khan; Ayesha Latif; Muhammad Au Khan; Bushra Tabassum; Ahmed A. Shahid; Ahmed U. Zafar; Tayyab Husnain (Biologia, 2015)

Short-horned grasshopper subfamilies feed at different rates on big bluestem and switchgrass cultivars - Muhammad Irfan Ullah; Fatima Mustafa; William W. Hoback; Mathew L. Brust; Kerri M. Farnsworth-Hoback; John E. Foster (Biologia, 2015)

Effect of Beauveria bassiana infection on the feeding performance and antioxidant defence of red palm weevil, Rhynchophorus ferrugineus - Abid Hussain; Muhammad Rizwan-ul-Haq; Hassan Al-Ayedh; Sohail Ahmed; Ahmed Mohammed Al-Jabr (BioControl, 2015)

A case study of Precambrian to Eocene sediments’ hydrocarbon potential assessment in Central Indus Basin of Pakistan - Shazia Asim; Peimin Zhu; Shahid Nadeem Qureshi; Muhammad Tayyab Naseer (Arabian Journal of Geosciences, 2015)

Determination of arsenic contents in groundwater of District Rahim Yar Khan Southern Punjab, Pakistan - Muhammad Tariq Mahar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Mushtaq Ahmad Baloch (Arabian Journal of Geosciences, 2015)

Prediction of permeability anisotropy using Dar-Zarrouk parameters of deep resistivity logs: a case study in the northern Western Desert of Egypt - Mohamed Attwa; Muhammad Nabih (Arabian Journal of Geosciences, 2015)

UML-based requirement modeling of Web online synchronous collaborative public participatory GIS - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2015)

A heavy metal tolerant novel bacterium, Bacillus malikii sp. nov., isolated from tannery effluent wastewater - Saira Abbas; Iftikhar Ahmed; Takuji Kudo; Muhammad Iqbal; Yong-Jae Lee; Toru Fujiwara; Moriya Ohkuma (Antonie van Leeuwenhoek, 2015)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

Distribution of Natural Uranium in Surface and Groundwater Resources: A Review - Amir Waseem; Hussain Ullah; Muhammad Khawar Rauf; Ijaz Ahmad (Critical Reviews in Environmental Science and Technology, 2015)

Estimation of Water Resources Availability and Mini-Hydro Productivity in High-Altitude Scarcely-Gauged Watershed - Muhammad Azmat; Francesco Laio; Davide Poggi (Water Resources Management, 2015)

Interactive effects of melatonin and light on growth parameters and biochemical markers in adventitious roots of Withania somnifera L. - Muhammad Adil; Bilal Haider Abbasi; Tariq Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

A streptozotocin-induced diabetic neuropathic pain model for static or dynamic mechanical allodynia and vulvodynia: validation using topical and systemic gabapentin - Gowhar Ali; Fazal Subhan; Muzaffar Abbas; Jehan Zeb; Muhammad Shahid; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Local site effects on seismic ground response of major cities in UAE - Magdi El-Emam; Zahid Khan; Jamal Abdalla; Muhammad Irfan (Natural Hazards, 2015)

Microwave Assisted Synthesis, Physicochemical, Photophysical, Single Crystal X-ray and DFT Studies of Novel Push–Pull Chromophores - Salman A. Khan; Abdullah M. Asiri; Hadi Mussa Basisi; Muhammad Nadeem Arshad; Kamlesh Sharma (Journal of Fluorescence, 2015)

Empirical evidence of cold stress induced cell mediated and humoral immune response in common myna (Sturnus tristis) - Mansur A. Sandhu; Anila Zaib; Muhammad S. Anjum; Mazhar Qayyum (International Journal of Biometeorology, 2015)

Mapping QTLs associated with root traits using two different populations in wheat (Triticum aestivum L.) - Muhammad Rezaul Kabir; Gang Liu; Panfeng Guan; Fei Wang; Abul Awlad Khan; Zhongfu Ni; Yingyin Yao; Zhaorong Hu; Mingming Xin; Huiru Peng; Qixin Sun (Euphytica, 2015)

Development of sediment load estimation models by using artificial neural networking techniques - Muhammad Hassan; M. Ali Shamim; Ali Sikandar; Imran Mehmood; Imtiaz Ahmed; Syed Zishan Ashiq; Anwar Khitab (Environmental Monitoring and Assessment, 2015)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Effect of inorganic amendments for in situ stabilization of cadmium in contaminated soils and its phyto-availability to wheat and rice under rotation - Muhammad Zia-ur Rehman; Muhammad Rizwan; Abdul Ghafoor; Asif Naeem; Shafaqat Ali; Muhammad Sabir; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2015)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Reliance of physico-mechanical properties on petrographic characteristics: consequences from the study of Utla granites, north-west Pakistan - Muhammad Sajid; Mohammad Arif (Bulletin of Engineering Geology and the Environment, 2015)

Effect of Selenium Supplementation on Apoptosis and Cell Cycle Blockage of Renal Cells in Broilers Fed a Diet Containing Aflatoxin B1 - Zhengqiang Yu; Fengyuan Wang; Na Liang; Chuhan Wang; Xi Peng; Jing Fang; Hengmin Cui; Muhammad Jameel Mughal; Weimin Lai (Biological Trace Element Research, 2015)

Effects of in situ habitat quality and landscape characteristics in the oil palm agricultural matrix on tropical understory birds, fruit bats and butterflies - Badrul Azhar; Chong Leong Puan; Najjib Aziz; Muhammad Sainuddin; Nurfatin Adila; Sohaimi Samsuddin; Siti Asmah; Muhamad Syafiq; Syafiq A. Razak; Ahmad Hafizuddin; Ainil Hawa; Syari Jamian (Biodiversity and Conservation, 2015)

Numerical simulation of methane plumes based on effective medium theory - Jiachun You; Canping Li; Lifang Cheng; Xuewei Liu; Muhammad irfan Ehsan (Arabian Journal of Geosciences, 2015)

Petrogenetic evolution of pegmatites of the Shigar Valley, Skardu, Gilgit-Baltistan, Pakistan - Muhammad Hassan Agheem; Mohammad Tahir Shah; Tahseenullah Khan; Mamoru Murata; Humaira Dars; Muhammad Zafar (Arabian Journal of Geosciences, 2015)

3D Reconstruction of Chick Embryo Vascular Geometries Using Non-invasive High-Frequency Ultrasound for Computational Fluid Dynamics Studies - Germaine Xin Yi Tan; Muhammad Jamil; Nicole Gui Zhen Tee; Liang Zhong; Choon Hwai Yap (Annals of Biomedical Engineering, 2015)

A novel protein quality control mechanism contributes to heat shock resistance of worldwide‐distributed P seudomonas aeruginosa clone C strains - Changhan Lee; Edvard Wigren; Janja Trček; Verena Peters; Jihong Kim; Muhammad Sharif Hasni; Manfred Nimtz; Ylva Lindqvist; Chankyu Park; Ute Curth; Heinrich Lünsdorf; Ute Römling (Environmental Microbiology, 2015)
Summary P seudomonas aeruginosa is a highly successful nosocomial pathogen capable of causing a wide variety of infections with clone C strains most prevalent worldwide. In this study, we initially characterize a molecular mechanism of survival unique to clone C strains. We identified a P . aeruginosa clone C ‐specific genomic island ( PACGI ‐1) that contains the highly expressed small heat shock protein sHsp 20c, the founding member of a novel subclass of class B bacterial small heat shock proteins. sHsp 20c and adjacent gene products are involved in resistance against heat shock. Heat stable sHsp 20c is unconventionally expressed in stationary phase in a wide temperature range from 20 to 42°C. Purified sHsp 20c has characteristic features of small heat shock protein class B as it is monodisperse, forms sphere‐like 24‐meric oligomers and exhibits significant chaperone activity. As the P . aeruginosa clone C population is significantly more heat shock resistant than genetically unrelated P . aeruginosa strains without sHsp20c, the horizontally acquired shsp20c operon might contribute to the survival of worldwide‐distributed clone C strains.

Bioanalytical evaluation of Cinnamomum zeylanicum essential oil - Muhammad Saleem; Haq Nawaz Bhatti; Muhammad Idrees Jilani; Muhammad Asif Hanif (Natural Product Research, 2015)

Monthly Runoff Regime Regionalization Through Dissimilarity-Based Methods - Muhammad Uzair Qamar; Daniele Ganora; Pierluigi Claps (Water Resources Management, 2015)

Mapping of a new stem rust resistance gene Sr49 in chromosome 5B of wheat - Urmil K. Bansal; Sher Muhammad; Kerrie L. Forrest; Matthew J. Hayden; Harbans S. Bariana (Theoretical and Applied Genetics, 2015)

Pirin1 Is a Non-Circadian Regulated Transcript and Protein, but Highly Responsive to Light/Dark Periods in the Seed-to-Seedling Transition in Arabidopsis thaliana - Danielle A. Orozco-Nunnelly; Durreshahwar Muhammad; Vaiva Liakaite; Stefan J. Green; Katherine M. Warpeha (Plant Molecular Biology Reporter, 2015)

Spatio-temporal variations of b-value in and around north Pakistan - Khaista Rehman; Asghar Ali; Sajjad Ahmed; Wajid Ali; Aamir Ali; Muhammad Younis Khan (Journal of Earth System Science, 2015)

Increase in telencephalic dopamine and cerebellar norepinephrine contents by hydrostatic pressure in goldfish: the possible involvement in hydrostatic pressure-related locomotion - Taro Ikegami; Akihiro Takemura; Eunjung Choi; Atsushi Suda; Shozo Tomonaga; Muhammad Badruzzaman; Mitsuhiro Furuse (Fish Physiology and Biochemistry, 2015)

Food security policy assessment in the Punjab, Pakistan: effectiveness, distortions and their perceptions - Muhammad Khalid Bashir; Steven Schilizzi (Food Security, 2015)

Use of statistical and GIS techniques to assess and predict concentrations of heavy metals in soils of Lahore City, Pakistan - Nayab Alam; Sajid Rashid Ahmad; Abdul Qadir; Muhammad Imran Ashraf; Calvin Lakhan; V. Chris Lakhan (Environmental Monitoring and Assessment, 2015)

Reverse ion exchange as a major process controlling the groundwater chemistry in an arid environment: a case study from northwestern Saudi Arabia - Faisal K. Zaidi; Yousef Nazzal; Muhammad Kamran Jafri; Muhammad Naeem; Izrar Ahmed (Environmental Monitoring and Assessment, 2015)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Consumer purchase intention towards environmentally friendly vehicles: an empirical investigation in Kuala Lumpur, Malaysia - Rafia Afroz; Muhammad Mehedi Masud; Rulia Akhtar; Md. Ashraful Islam; Jarita Bt Duasa (Environmental Science and Pollution Research, 2015)

Effect of Rht alleles on wheat grain yield and quality under high temperature and drought stress during booting and anthesis - Fahad Alghabari; Muhammad Zahid Ihsan; Saddam Hussain; Ghulam Aishia; Ihsanullah Daur (Environmental Science and Pollution Research, 2015)

FRET-based genetically-encoded sensors for quantitative monitoring of metabolites - Mohd. Mohsin; Altaf Ahmad; Muhammad Iqbal (Biotechnology Letters, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Correlation of manganese with thyroid function in females having hypo- and hyperthyroid disorders - Nusrat Shahab Memon; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Oan Muhammad Sahito; Shahnawaz Baloch; Muhammad Waris (Biological Trace Element Research, 2015)

Synthesis, characterization and theoretical calculations of (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride complexes: in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; Muhammad Altaf; Abdulaziz A. Al-Saadi; Abdel-Nasser Kawde; Saleh Altuwaijri; Saeed Ahmad; Anvarhusein A. Isab (BioMetals, 2015)

Whole-exome sequencing identifies a novel LRAT mutation underlying retinitis punctata albescens in a consanguineous Pakistani family - Musharraf Jelani; Miyeon Jeon; Obaid Ur Rahman; Fazal Rahim; Muhammad Naeem; Changsoo Kang (Genes & Genomics, 2015)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Stratigraphic characterization and structural analysis of the northwestern Hazara Ranges across Panjal Thrust, northern Pakistan - Muhammad Qasim; Muhammad Asif Khan; Muhammad Haneef (Arabian Journal of Geosciences, 2015)

Geochemistry and petrogenesis of Oligocene volcaniclastic rocks from the Chagai arc: implications for the emplacement of porphyry copper deposits - Rehanul Haq Siddiqui; Muhammad Asif Khan; Muhammad Qasim Jan; Mohammad Ishaq Kakar; Andrew C. Kerr (Arabian Journal of Geosciences, 2015)

Integrated study of seismic and well data for porosity estimation using multi-attribute transforms: a case study of Boonsville Field, Fort Worth Basin, Texas, USA - Muhammad Naeem; Hesham M. El-Araby; Mohammed Khalil Khalil; Muhammad Kamran Jafri; Farhan Khan (Arabian Journal of Geosciences, 2015)

Effect of pH on the static adsorption of foaming surfactants on Malaysian sandstone - Muhammad Mushtaq; Isa M. Tan; Umer Rashid; Muhammad Sagir; Mudassar Mumtaz (Arabian Journal of Geosciences, 2015)

Effect of water deficit during vegetative growth periods on post-anthesis photosynthetic capacity and grain yield in winter wheat (Triticum aestivum L.) - Yakun Cui; Zhongwei Tian; Xu Zhang; Abid Muhammad; Huimin Han; Dong Jiang; Weixing Cao; Tingbo Dai (Acta Physiologiae Plantarum, 2015)

Solvent Effect on the Photolysis of Riboflavin - Iqbal Ahmad; Zubair Anwar; Sofia Ahmed; Muhammad Ali Sheraz; Raheela Bano; Ambreen Hafeez (AAPS PharmSciTech, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

Abiotic and Biotic Processes Governing the Fate of Phenylurea Herbicides in Soils: A Review - Sabir Hussain; Muhammad Arshad; Dirk Springael; Sebastian R. SøRensen; Gary D. Bending; Marion Devers-Lamrani; Zahid Maqbool; Fabrice Martin-Laurent (Critical Reviews in Environmental Science and Technology, 2015)

Isolation, structure elucidation and enzyme inhibition studies of a new hydroxy ester and other compounds from Berberis jaeschkeana Schneid stem - Muhammad Alamzeb; M. Rafiullah Khan; Mamoon-Ur-Rashid; Saqib Ali; Ashfaq Ahmad Khan (Natural Product Research, 2015)

Plant growth-promoting potential of endophytic fungi isolated from Solanum nigrum leaves - Abdur Rahim Khan; Ihsan Ullah; Muhammad Waqas; Raheem Shahzad; Sung-Jun Hong; Gun-Seok Park; Byung Kwon Jung; In-Jung Lee; Jae-Ho Shin (World Journal of Microbiology and Biotechnology, 2015)

Zinc-induced modulation of some biochemical parameters in a high- and a low-zinc-accumulating genotype of Cicer arietinum L. grown under Zn-deficient condition - Shadab Naseer Siddiqui; Shahid Umar; Muhammad Iqbal (Protoplasma, 2015)

Identification and functional characterization of the BBX24 promoter and gene from chrysanthemum in Arabidopsis - Muhammad Imtiaz; Yingjie Yang; Ruixue Liu; Yanjie Xu; Muhammad Ali Khan; Qian Wei; Junping Gao; Bo Hong (Plant Molecular Biology, 2015)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

Cancer initiating properties of erythrosine supplemented with sub necrotic dose of diethyl nitrosamine: potential effects on biochemical parameters of liver, Vitamin C and E - Firoz Anwar; Rajbala Singh; Gohar Mushtaq; Abdul Rehman Al-Maliki; Abdullah Sabih; F. A. Al-Abbasi; Aftab Ahmad; Muhammad Afzal; Imran Kazmi; Ruqaiyah Khan (Molecular & Cellular Toxicology, 2015)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

The importance of alternative host plants as reservoirs of the cotton leaf hopper, Amrasca devastans, and its natural enemies - Rabia Saeed; Muhammad Razaq; Ian C. W. Hardy (Journal of Pest Science, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Characterization of N2O emission and associated bacterial communities from the gut of wood-feeding termite Nasutitermes voeltzkowi - Muhammad Zeeshan Majeed; Edouard Miambi; Muhammad Asam Riaz; Alain Brauman (Folia Microbiologica, 2015)

The uptake and bioaccumulation of heavy metals by food plants, their effects on plants nutrients, and associated health risk: a review - Anwarzeb Khan; Sardar Khan; Muhammad Amjad Khan; Zahir Qamar; Muhammad Waqas (Environmental Science and Pollution Research, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Assessment of heavy metals and metalloids in tissues of two frog species: Rana tigrina and Euphlyctis cyanophlyctis from industrial city Sialkot, Pakistan - Irfan Zia Qureshi; Zeshan Kashif; Muhammad Zaffar Hashmi; Xiaomei Su; Riffat Naseem Malik; Kalim Ullah; Jinxing Hu; Muhammad Dawood (Environmental Science and Pollution Research, 2015)

Improvement in phytoremediation potential of Solanum nigrum under cadmium contamination through endophytic-assisted Serratia sp. RSC-14 inoculation - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Gun-Seok Park; Muhammad Waqas; Sung-Jun Hong; Byung Kwon Jung; Yunyoung Kwak; In-Jung Lee; Jae-Ho Shin (Environmental Science and Pollution Research, 2015)

Safe use of Cry genes in genetically modified crops - M. Rahman; Muhammad Zaman; Tayyaba Shaheen; Samra Irem; Yusuf Zafar (Environmental Chemistry Letters, 2015)

Modulations in plant water relations and tissue-specific osmoregulation by foliar-applied ascorbic acid and the induction of salt tolerance in maize plants - Sidra Jamil; Qasim Ali; Muhammad Iqbal; Muhammad Tariq Javed; Wasif Iftikhar; Faisal Shahzad; Rashida Perveen (Brazilian Journal of Botany, 2015)

Nitrate accumulation pattern in Brassica under nitrogen treatments - Samina Mazahar; Ovais Sareer; Shahid Umar; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Identification of quantitative trait loci for Na+, K+ and Ca++ accumulation traits in rice grown under saline conditions using F2 mapping population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2015)

Exogenous application of trehalose alters growth, physiology and nutrient composition in radish (Raphanus sativus L.) plants under water-deficit conditions - Nudrat Aisha Akram; Sidra Noreen; Tabassum Noreen; Muhammad Ashraf (Brazilian Journal of Botany, 2015)

Heterogeneous expansion of end-moraine dammed lakes in the Hindukush-Karakoram-Himalaya ranges of Pakistan during 2001–2013 - Arshad Ashraf; Rozina Naz; Muhammad Bilal Iqbal (Journal of Mountain Science, 2015)

Germline mutations predisposing to non-small cell lung cancer - Gerald H. Clamon; Aaron D. Bossler; Taher Abu Hejleh; Muhammad Furqan (Familial Cancer, 2015)

The effect of gestational diabetes on proliferation capacity and viability of human umbilical cord-derived stromal cells - Nadia Wajid; Rashida Naseem; Sanam Saiqa Anwar; Sana Javaid Awan; Muhammad Ali; Sara Javed; Fatima Ali (Cell and Tissue Banking, 2015)

An optimal approach for the development of precise regional geoid in Pakistan through a comparative study with least square collocation and FFT techniques - Sadiq Muhammad; Ahmad Zulfiqar (Arabian Journal of Geosciences, 2015)

Usability evaluation of collaborative PPGIS-GeoCWMI for supporting public participation during municipal planning and management services - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2015)

Losses of soil carbon by converting tropical forest to plantations: erosion and decomposition estimated by δ 13 C - Thomas Guillaume; Muhammad Damris; Yakov Kuzyakov (Global Change Biology, 2015)
Indonesia lost more tropical forest than all of Brazil in 2012, mainly driven by the rubber, oil palm, and timber industries. Nonetheless, the effects of converting forest to oil palm and rubber plantations on soil organic carbon ( SOC ) stocks remain unclear. We analyzed SOC losses after lowland rainforest conversion to oil palm, intensive rubber, and extensive rubber plantations in Jambi Province on Sumatra Island. The focus was on two processes: (1) erosion and (2) decomposition of soil organic matter. Carbon contents in the Ah horizon under oil palm and rubber plantations were strongly reduced up to 70% and 62%, respectively. The decrease was lower under extensive rubber plantations (41%). On average, converting forest to plantations led to a loss of 10 Mg C ha −1 after about 15 years of conversion. The C content in the subsoil was similar under the forest and the plantations. We therefore assumed that a shift to higher δ 13 C values in plantation subsoil corresponds to the losses from the upper soil layer by erosion. Erosion was estimated by comparing the δ 13 C profiles in the soils under forest and under plantations. The estimated erosion was the strongest in oil palm (35 ± 8 cm) and rubber (33 ± 10 cm) plantations. The 13 C enrichment of SOC used as a proxy of its turnover indicates a decrease of SOC decomposition rate in the Ah horizon under oil palm plantations after forest conversion. Nonetheless, based on the lack of C input from litter, we expect further losses of SOC in oil palm plantations, which are a less sustainable land use compared to rubber plantations. We conclude that δ 13 C depth profiles may be a powerful tool to disentangle soil erosion and SOC mineralization after the conversion of natural ecosystems conversion to intensive plantations when soils show gradual increase of δ 13 C values with depth.

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Potato Starch as a Coagulant for Dye Removal from Textile Wastewater - Muhammad Shahzad Zafar; Muhammad Tausif; Muhammad Mohsin; Syed Waqas Ahmad; Muhammad Zia-ul-Haq (Water, Air, & Soil Pollution, 2015)

Urban Residential Water Demand Prediction Based on Artificial Neural Networks and Time Series Models - Muhammad A. Al-Zahrani; Amin Abo-Monasar (Water Resources Management, 2015)

Seroprevalence of Bluetongue virus in domestic yaks (Bos grunniens) in Tibetan regions of China based on circulating antibodies - Jiakui Li; Kun Li; Muhammad Shahzad; Zhaoqing Han; Fazul Nabi; Jianfeng Gao; Jinmei Han (Tropical Animal Health and Production, 2015)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Serological prevalence of contagious bovine pleuropneumonia in agro-pastoral areas of Nigeria - Abubakar Suleiman; Mohammed Bello; Asabe A. Dzikwi; Ahmad Muhammad Talba; Hafsat Ali Grema; Yaqub Ahmed Geidam (Tropical Animal Health and Production, 2015)

Synthesis and evaluation of unsymmetrical heterocyclic thioureas as potent β-glucuronidase inhibitors - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Khalid Mohammed Khan; Uzma Salar; Syed Muhammad Kashif; Fazal Rahim; Yawar Latif (Medicinal Chemistry Research, 2015)

The chemical inhibitors of cellular death, PJ34 and Necrostatin-1, down-regulate IL-33 expression in liver - Muhammad Imran Arshad; Claire Piquet-Pellorce; Aveline Filliol; Annie L’Helgoualc’h; Catherine Lucas-Clerc; Sandrine Jouan-Lanhouet; Marie-Thérèse Dimanche-Boitrel; Michel Samson (Journal of Molecular Medicine, 2015)

Methyl jasmonate enhances phlorotannin production in the brown seaweed Ecklonia cava - Muhammad Tanvir Hossain Chowdhury; Ji-Young Cho; Dong-Hyun Ahn; Yong-Ki Hong (Journal of Applied Phycology, 2015)

Crossability among modern roses and heterosis of quantitative and qualitative traits in hybrids - Muhammad Nadeem; Adnan Younis; Atif Riaz; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2015)

Genetic analysis suggests a shared origin of Punica granatum cultivars in Oman with cultivars from the center of origin, Iran - Abdullah M. Al-Sadi; Ahmed R. AL-Fahdi; Rashid A. Al-Yahyai; Aisha G. Al-Ghaithi; Fahad A. Al-Said; Muhammad J. Soleiman (Genetic Resources and Crop Evolution, 2015)

Cempedak durian as a potential biosorbent for the removal of Brilliant Green dye from aqueous solution: equilibrium, thermodynamics and kinetics studies - Muhammad Khairud Dahri; Linda B. L. Lim; Chan Chin Mei (Environmental Monitoring and Assessment, 2015)

Erratum to: Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Fluoride estimation and its correlation with other physicochemical parameters in drinking water of some areas of Balochistan, Pakistan - Tasawar Ali Chandio; Muhammad Nasiruddin Khan; Anila Sarwar (Environmental Monitoring and Assessment, 2015)

Estimation of lead in biological samples of oral cancer patients chewing smokeless tobacco products by ionic liquid-based microextraction in a single syringe system - Sadaf S. Arain; Tasneem G. Kazi; Asma J. Arain; Hassan I. Afridi; Muhammad B. Arain; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Mariam S. Arain (Environmental Science and Pollution Research, 2015)

Application of sewage sludge and sewage sludge biochar to reduce polycyclic aromatic hydrocarbons (PAH) and potentially toxic elements (PTE) accumulation in tomato - Muhammad Waqas; Gang Li; Sardar Khan; Isha Shamshad; Brian J. Reid; Zahir Qamar; Cai Chao (Environmental Science and Pollution Research, 2015)

The battle of health with environmental evils of Asian countries: promises to keep - Muhammad Imran Qureshi; Noor Ullah Khan; Amran Md. Rasli; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Dissemination via the lymphatic or angiogenic route impacts the pathology, microenvironment and hypoxia-related drug response of lung metastases - Roben G. Gieling; Richard J. Fitzmaurice; Brian A. Telfer; Muhammad Babur; Kaye J. Williams (Clinical & Experimental Metastasis, 2015)

Isolation of buffalo poxvirus from clinical case and variations in the genetics of the B5R gene over fifty passages - Mohsan Ullah Goraya; Zafar ul Ahsan Qureshi; Muhammad Abbas; Muhammad Ashraf; Muhammad Munir (Virus Genes, 2015)

Human aging in the post-GWAS era: further insights reveal potential regulatory variants - Syed Aleem Haider; Muhammad Faisal (Biogerontology, 2015)

Skin pentosidine and telomere length do not covary with age in a long-lived seabird - Kalev Rattiste; Hillar Klandorf; Janek Urvik; Tuul Sepp; Muhammad Asghar; Dennis Hasselquist; Crissa Cooey; Peeter Hõrak (Biogerontology, 2015)

The influence of tree architecture, forest remnants, and dispersal syndrome on roadside epiphyte diversity in a highly urbanized tropical environment - Muhammad Izuddin; Edward L. Webb (Biodiversity and Conservation, 2015)

The Early Cambrian Khewra Sandstone, Salt Range, Pakistan: endorsing southern Indian provenance - Mubashir Jehangiri; Muhammad Hanif; Muhammad Arif; Irfan U. Jan; Sajjad Ahmad (Arabian Journal of Geosciences, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Origin of the mafic dykes in Nagarparker area of Pakistan - Tahseenullah Khan; Mamoru Murata; Muhammad Zafar; Hafiz Ur Rehman (Arabian Journal of Geosciences, 2015)

Larvicidal activity of endophytic fungal extract of Cochliobolus spicifer (Pleosporales: Pleosporaceae) on Aedes caspius and Culex pipiens (Diptera: Culicidae) - Nael Abutaha; Ashraf M. A. Mashaly; Fahd A. Al-Mekhlafi; Muhammed Farooq; Mohammed Al-shami; Muhammad A. Wadaan (Applied Entomology and Zoology, 2015)

An insight into cotton genetic engineering (Gossypium hirsutum L.): current endeavors and prospects - Allah Bakhsh; Emine Anayol; Sancar Fatih Özcan; Tahira Hussain; Muhammad Aasim; Khalid Mahmood Khawar; Sebahattin Özcan (Acta Physiologiae Plantarum, 2015)

Priming-induced antioxidative responses in two wheat cultivars under saline stress - Faisal Islam; Tahira Yasmeen; Shafaqat Ali; Basharat Ali; Muhammad A. Farooq; Rafaqat A. Gill (Acta Physiologiae Plantarum, 2015)

Direct detection of saponins in crude extracts of soapnuts by FTIR - Meshari Saad Almutairi; Muhammad Ali (Natural Product Research, 2015)

Equity in Whom Gets Studied: A Systematic Review Examining Geographical Region, Gender, Commodity, and Employment Context in Research of Low Back Disorders in Farmers - Catherine Trask; Muhammad Idress Khan; Olugbenga Adebayo; Catherine Boden; Brenna Bath (Journal of Agromedicine, 2015)

Photosynthesis and growth responses of mustard (Brassica juncea L. cv Pusa Bold) plants to free air carbon dioxide enrichment (FACE) - Kamal Ruhil; Sheeba; Altaf Ahmad; Muhammad Iqbal; Baishnab C. Tripathy (Protoplasma, 2015)

Synthesis of phenyl thiazole hydrazones and their activity against glycation of proteins - Khalid Mohammed Khan; Muhammad Irfan; Mahwish Ashraf; Muhammad Taha; Syed Muhammad Saad; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Optical, Electrochemical and Thermoanalytical Investigations on Newly-Synthesized Perylene-3,4,9,10-Dianhydride Fluorescent Dyes - Aamer Saeed; Ghulam Shabir; Muhammad Arshad (Journal of Fluorescence, 2015)

Combining ability through line × tester analysis for phenological, seed yield, and oil traits in sunflower (Helianthus annuus L.) - Shahnaz Memon; Muhammad Jurial Baloch; Gul Muhammad Baloch; Wajid Ali Jatoi (Euphytica, 2015)

Production of Brassica tri-genomic vegetable germplasm by hybridisation between tuber mustard (Brassica juncea) and red cabbage (B. oleracea) - Junxing Li; Linli Rao; Qiufeng Meng; Muhammad Awais Ghani; Liping Chen (Euphytica, 2015)

Oxidative injury and antioxidant enzymes regulation in arsenic-exposed seedlings of four Brassica napus L. cultivars - Muhammad A. Farooq; Lan Li; Basharat Ali; Rafaqat A. Gill; Jian Wang; Shafaqat Ali; Muhammad B. Gill; Weijun Zhou (Environmental Science and Pollution Research, 2015)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

Gibberellic acid in combination with pressmud enhances the growth of sunflower and stabilizes chromium(VI)-contaminated soil - Muhammad Saleem; Hafiz Naeem Asghar; Muhammad Yahya Khan; Zahir Ahmad Zahir (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

Hydrological response to environment change in Himalayan watersheds: Assessment from integrated modeling approach - Zulfiqar Ahmad; Arshad Ashraf; Muhammad Zaheer; Humaira Bashir (Journal of Mountain Science, 2015)

Production of human interferon alpha-2b in Escherichia coli and removal of N-terminal methionine utilizing archaeal methionine aminopeptidase - Amina Arif; Qura-Tul-Ann A. Gardner; Naeem Rashid; Muhammad Akhtar (Biologia, 2015)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

Structural styles, hydrocarbon prospects, and potential in the Salt Range and Potwar Plateau, north Pakistan - Ishtiaq A. K. Jadoon; Matthias Hinderer; Beenish Wazir; Rizwan Yousaf; Sher Bahadar; Muhammad Hassan; Zeeshan-ul-Hassan Abbasi; Sidra Jadoon (Arabian Journal of Geosciences, 2015)

A GIS-based stream sediment geochemical model for gold and base metal exploration in remote areas of northern Pakistan - Liaqat Ali; Charlie John Moon; Ben James Williamson; Muhammad Tahir Shah; Seema Anjum Khattak (Arabian Journal of Geosciences, 2015)

Geochemical and organic petrographic characteristics of low-rank coals from Thar coalfield in the Sindh Province, Pakistan - Abrar Ahmad; Mohammed Hail Hakimi; Muhammad Nawaz Chaudhry (Arabian Journal of Geosciences, 2015)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

Evaluation of weather research and forecasting model for the assessment of wind resource over Gharo, Pakistan - Muhammad Amjad; Qudsia Zafar; Firdos Khan; Muhammad Munir Sheikh (International Journal of Climatology, 2015)
Weather research and forecasting (WRF) model is the state‐of‐the‐art mesoscale model that could be used as a guideline to effectively assess the wind resource of Gharo wind station lying in the coastal belt of Pakistan. The anemometer heights of 10 and 30 m for the year 2005 have been used to study the wind profile of the region for summer (June, July, August, September) and winter (December, January, February, March). The study uses an innovative approach for model comparisons, i.e. an eta‐half level is added in the model on 60 m height and is interpolated to 30 m height by using well known power law. This is done by studying the diurnal variation of wind shear for the whole year of 2005 in order to reduce maximum possible interpolation error. For both seasons, the error measures of mean bias error (MBE), mean absolute error (MAE) and root mean square error (RMSE) of 30 m interpolated data were found lower than 10 m height data with increased correlation ( r ). A bias correction methodology (best easy systematic estimator) was further applied over the model output showing a significant improvement toward MBE, MAE and RMSE reduction, i.e. up to 99%, 73% and 68% on 10 m height and 99%, 51% and 46% on 30 m height. Errors were reduced more for summer than winter. The selected bias correction methodology was thus found to be highly applicable for both model heights. The wind energy assessment of Gharo wind station from the corrected model simulation showed summer having more potential for wind energy than winter with an estimated energy of up to 1000 MWh.

Cytotoxic, antibacterial and antioxidant activities of extracts of the bark of Melia azedarach (China Berry) - Muhammad Zahoor; Manzoor Ahmed; Sumaira Naz; Musarrat Ayaz (Natural Product Research, 2015)

Process optimisation for the biosynthesis of cellulase by Bacillus PC-BC6 and its mutant derivative Bacillus N3 using submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Afshan Kaleem (Natural Product Research, 2015)

Tomato ( Solanum lycopersicum ) Carotenoids and Lycopenes Chemistry; Metabolism, Absorption, Nutrition, and Allied Health Claims—A Comprehensive Review - Rashida Perveen; Hafiz Ansar Rasul Suleria; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Sarfraz Ahmad (Critical Reviews in Food Science and Nutrition, 2015)

Application of Short-Offset TEM (SOTEM) Technique in Mapping Water-Enriched Zones of Coal Stratum, an Example from East China - Wei-ying Chen; G. Q. Xue; Younis Khan Muhammad; L. J. Gelius; Nan-nan Zhou; Hai Li; Hua-sen Zhong (Pure and Applied Geophysics, 2015)

Introduction of geospatial perspective to the ecology of fish-habitat relationships in Indonesian coral reefs: A remote sensing approach - Shuhei Sawayama; Nurjannah Nurdin; Muhammad Akbar AS; Shingo X. Sakamoto; Teruhisa Komatsu (Ocean Science Journal, 2015)

Detecting areas affected by flood using multi-temporal ALOS PALSAR remotely sensed data in Karawang, West Java, Indonesia - Fajar Yulianto; Parwati Sofan; Any Zubaidah; Kusumaning Ayu Dyah Sukowati; Junita Monika Pasaribu; Muhammad Rokhis Khomarudin (Natural Hazards, 2015)

Association of TLR1, TLR2, TLR4, TLR6, and TIRAP polymorphisms with disease susceptibility - Mamoona Noreen; Muhammad Arshad (Immunologic Research, 2015)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Exploring factors influencing farmers’ willingness to pay (WTP) for a planned adaptation programme to address climatic issues in agricultural sectors - Adeel Ahmed; Muhammad Mehedi Masud; Abul Quasem Al-Amin; Siti Rohani Binti Yahaya; Mahfuzur Rahman; Rulia Akhtar (Environmental Science and Pollution Research, 2015)

Effect of plant growth-promoting rhizobacteria inoculation on cadmium (Cd) uptake by Eruca sativa - Muhammad Aqeel Kamran; Jabir Hussain Syed; Syed Ali Musstjab Akber Shah Eqani; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Exogenous application of silicon at the boot stage decreases accumulation of cadmium in wheat (Triticum aestivum L.) grains - Iqbal Hussain; Muhammad Arslan Ashraf; Rizwan Rasheed; Anum Asghar; Muhammad Asim Sajid; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Lateral Meristems Responsible for Secondary Growth of the Monocotyledons: A Survey of the State of the Art - Joanna Jura-Morawiec; Mirela Tulik; Muhammad Iqbal (The Botanical Review, 2015)

Biosorption of heavy metals from aqueous solutions using indigenous and modified lignocellulosic materials - Muhammad Salman; Makshoof Athar; Umar Farooq (Reviews in Environmental Science and Bio/Technology, 2015)

An appraisal on the occurrence of foot-and-mouth disease virus serotypes in cattle and buffaloes, Pakistan - Muhammad Abubakar; Ehtisham-ul-Haq Khan; Muhammad Javed Arshed; Jose Gonzales; Giancarlo Ferrari; Manzoor Hussain; Qurban Ali (Archives of Virology, 2015)

Membrane protein profiling of Acidovorax avenae subsp. avenae under various growth conditions - Bin Li; Li Wang; Muhammad Ibrahim; Mengyu Ge; Yanli Wang; Shazia Mannan; Muhammad Asif; Guochang Sun (Archives of Microbiology, 2015)

Impact of rapid urbanization on microclimate of urban areas of Pakistan - Adnan Ahmad Tahir; Adnan Muhammad; Qaisar Mahmood; Sheikh Saeed Ahmad; Zahid Ullah (Air Quality, Atmosphere & Health, 2015)

RETRACTED ARTICLE: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2015)

Physiological characterization of anaerobic ammonium oxidizing bacterium ‘ C andidatus J ettenia caeni’ - Muhammad Ali; Mamoru Oshiki; Takanori Awata; Kazuo Isobe; Zenichiro Kimura; Hiroaki Yoshikawa; Daisuke Hira; Tomonori Kindaichi; Hisashi Satoh; Takao Fujii; Satoshi Okabe (Environmental Microbiology, 2015)
Summary To date, six candidate genera of anaerobic ammonium‐oxidizing (anammox) bacteria have been identified, and numerous studies have been conducted to understand their ecophysiology. In this study, we examined the physiological characteristics of an anammox bacterium in the genus ‘ C andidatus J ettenia’. Planctomycete KSU ‐1 was found to be a mesophilic (20–42.5°C) and neutrophilic ( pH 6.5–8.5) bacterium with a maximum growth rate of 0.0020 h −1 . Planctomycete KSU ‐1 cells showed typical physiological and structural features of anammox bacteria; i.e. 29 N 2 gas production by coupling of 15 NH 4 + and 14 NO 2 − , accumulation of hydrazine with the consumption of hydroxylamine and the presence of anammoxosome. In addition, the cells were capable of respiratory ammonification with oxidation of acetate. Notably, the cells contained menaquinone‐7 as a dominant respiratory quinone. Proteomic analysis was performed to examine underlying core metabolisms, and high expressions of hydrazine synthase, hydrazine dehydrogenase, hydroxylamine dehydrogenase, nitrite/nitrate oxidoreductase and carbon monoxide dehydrogenase/acetyl‐ CoA synthase were detected. These proteins require iron or copper as a metal cofactor, and both were dominant in planctomycete KSU ‐1 cells. On the basis of these experimental results, we proposed the name ‘ C a . J ettenia caeni’ sp. nov. for the bacterial clade of the planctomycete KSU ‐1.

A new rosane-type diterpenoid from Stachys parviflora and its density functional theory studies - Umar Farooq; Khurshid Ayub; Muhammad Ali Hashmi; Rizwana Sarwar; Afsar Khan; Mumtaz Ali; Manzoor Ahmad; Ajmal Khan (Natural Product Research, 2015)

Arsenic Adsorption Using Palm Oil Waste Clinker Sand Biotechnology: an Experimental and Optimization Approach - Muhammad Abdur Rehman; Ismail Yusoff; Rasel Ahmmad; Yatimah Alias (Water, Air, & Soil Pollution, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Comparing Spatial Interpolation Schemes for Constructing a Flow Duration Curve in an Ungauged Basin - Muhammad Waseem; Ji-yae Shin; Tae-Woong Kim (Water Resources Management, 2015)

Groundwater modelling for need assessment of command scale conjunctive water use for addressing the exacerbating irrigation cost inequities in LBDC irrigation system, Punjab, Pakistan - Muhammad Basharat; Ata-ur-Rehman Tariq (Sustainable Water Resources Management, 2015)

WsMAGO2, a duplicated MAGO NASHI protein with fertility attributes interacts with MPF2-like MADS-box proteins - Humera Ihsan; Muhammad Ramzan Khan; Wajya Ajmal; Ghulam Muhammad Ali (Planta, 2015)

Growth, V uptake, and antioxidant enzymes responses of chickpea (Cicer arietinum L.) genotypes under vanadium stress - Muhammad Imtiaz; Shuxin Tu; Zhijian Xie; Dan Han; Muhammad Ashraf; Muhammad Shahid Rizwan (Plant and Soil, 2015)

Responses of rose RhACS1 and RhACS2 promoters to abiotic stresses in transgenic Arabidopsis thaliana - Muhammad Ali Khan; Yonglu Meng; Daofeng Liu; Hongshu Tang; Suhui Lü; Muhammad Imtiaz; Guimei Jiang; Peitao Lü; Yuqi Ji; Junping Gao; Nan Ma (Plant Cell Reports, 2015)

Effects of volume on travel distance of mass movements triggered by the 2005 Kashmir earthquake, in the Northeast Himalayas of Pakistan - Muhammad Basharat; Joachim Rohn (Natural Hazards, 2015)

Spatio-temporal characteristics of precipitation and drought in Balochistan Province, Pakistan - Muhammad Ashraf; Jayant K. Routray (Natural Hazards, 2015)

Multistatistical approaches for environmental geochemical assessment of pollutants in soils of Gadoon Amazai Industrial Estate, Pakistan - Rahib Hussain; Seema A. Khattak; Muhammad Tahir Shah; Liaqat Ali (Journal of Soils and Sediments, 2015)

Seasonal abundance of soil arthropods in relation to meteorological and edaphic factors in the agroecosystems of Faisalabad, Punjab, Pakistan - Muhammad Mussadiq Shakir; Sohail Ahmed (International Journal of Biometeorology, 2015)

Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

Water quality and sediment assessment of Manchar Lake, Sindh, Pakistan: after effects of the super flood of 2010 - Taj Muhammad Jahangir; Muhammad Yar Khuhawar; Sultan Mahmood Leghari; Muhammad Tariq Mahar; Khalida Parveen Mahar (Arabian Journal of Geosciences, 2015)

A new isoquinoline alkaloid with anti-microbial properties from Berberis jaeschkeana Schneid. var. jaeschkeana - Muhammad Alamzeb; M. Rafiullah Khan; Saqib Ali; Ashfaq Ahmad Khan (Natural Product Research, 2015)

Methane flux from paddy vegetated soil: a comparison between biogas digested liquid and chemical fertilizer - Ankit Singla; Suresh Kumar Dubey; Muhammad Aslam Ali; Kazuyuki Inubushi (Wetlands Ecology and Management, 2015)

Impacts of Prolonged Drought on Salt Accumulation in the Root Zone Due to Recycled Water Irrigation - Muhammad Muhitur Rahman; Dharma Hagare; Basant Maheshwari; Peter Dillon (Water, Air, & Soil Pollution, 2015)

Improved Runoff Estimation Using Event-Based Rainfall-Runoff Models - Muhammad Ajmal; Muhammad Waseem; Jae-Hyun Ahn; Tae-Woong Kim (Water Resources Management, 2015)

Geostatistical Simulation and Reconstruction of Porous Media by a Cross-Correlation Function and Integration of Hard and Soft Data - Pejman Tahmasebi; Muhammad Sahimi (Transport in Porous Media, 2015)

Triarylimidazoles-synthesis of 3-(4,5-diaryl-1H-imidazol-2-yl)-2-phenyl-1H-indole derivatives as potent α-glucosidase inhibitors - Sadia Naureen; Shazia Noreen; Areesha Nazeer; Muhammad Ashraf; Umber Alam; Munawar Ali Munawar; Misbahul Ain Khan (Medicinal Chemistry Research, 2015)

Synthesis, characterization and urease inhibition, in vitro anticancer and antileishmanial studies of Ni(II) complexes with N,N,N′-trisubstituted thioureas - Muhammad Khawar Rauf; Samad Yaseen; Amin Badshah; Sumera Zaib; Raffia Arshad; Imtiaz-ud-Din; Muhammad Nawaz Tahir; Jamshed Iqbal (JBIC Journal of Biological Inorganic Chemistry, 2015)

Endophytic infection alleviates biotic stress in sunflower through regulation of defence hormones, antioxidants and functional amino acids - Muhammad Waqas; Abdul Latif Khan; Muhammad Hamayun; Raheem Shahzad; Yoon-Ha Kim; Kyung-Sook Choi; In-Jung Lee (European Journal of Plant Pathology, 2015)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)

Phylogenetic characterization and novelty of organic sulphur metabolizing genes of Rhodococcus spp. (Eu-32) - Nasrin Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Shaun Heaphy (Biotechnology Letters, 2015)

Three gene products of a begomovirus–betasatellite complex restore expression of a transcriptionally silenced green fluorescent protein transgene in Nicotiana benthamiana - Muhammad Saeed; Gabi Krczal; Michael Wassenegger (Virus Genes, 2015)

Pro-environmental behavior and public understanding of climate change - Muhammad Mehedi Masud; Rulia Akhtar; Rafia Afroz; Abul Quasem Al-Amin; Fatimah Binti Kari (Mitigation and Adaptation Strategies for Global Change, 2015)

Response of nitrogen assimilating enzymes during in vitro culture of Argyrolobium roseum - Darima Habib; Muhammad Zia; Yamin Bibi; Bilal Haider Abbasi; Muhammad Fayyaz Chaudhary (Biologia, 2015)

Paenibacillus ginsengiterrae sp. nov., a ginsenoside-hydrolyzing bacteria isolated from soil of ginseng field - Md. Amdadul Huq; Yeon-Ju Kim; Van-An Hoang; Muhammad Zubair Siddiqi; Deok-Chun Yang (Archives of Microbiology, 2015)

Heterogeneous data management and modeling for the gravimetric geoid model: a review study in Pakistan - Muhammad Sadiq; Zulfiqar Ahmad (Arabian Journal of Geosciences, 2015)

Impact of uncertainty in remote sensing DEMs on topographic amplification of seismic response and Vs 30 - Muhammad Shafique; Mark van der Meijde (Arabian Journal of Geosciences, 2015)

Distribution of gold in different size fractions of stream sediments as a guide to bedrock gold mineralisation along the Shyok Suture Zone and adjacent areas of the Kohistan Island Arc, Pakistan - Liaqat Ali; Ben James Williamson; Charlie John Moon; Muhammad Tahir Shah; Seema Anjum Khattak (Arabian Journal of Geosciences, 2015)

First evidence of the analgesic activity of govaniadine, an alkaloid isolated from Corydalis govaniana Wall. - Naveed Muhammad; Ram Lal Shrestha; Achyut Adhikari; Abdul Wadood; Haroon Khan; Amir Zada Khan; Francesco Maione; Nicola Mascolo; Vincenzo De Feo (Natural Product Research, 2015)

Physico-chemical properties and cytotoxic potential of Cordyceps sinensis metabolites - Eun-Jeong Lee; Ka-Hee Jang; Seon-Young Im; Yoon-Kyung Lee; Muhammad Farooq; Rozbeh Farhoudi; Dong-Jin Lee (Natural Product Research, 2015)

mRNA secondary structure engineering of Thermobifida fusca endoglucanase (Cel6A) for enhanced expression in Escherichia coli - Imran Ali; Rehana Asghar; Sajjad Ahmed; Muhammad Sajjad; Muhammad Tariq; M. Waheed Akhtar (World Journal of Microbiology and Biotechnology, 2015)

Evaluating pasture and soil allowance of manganese for Kajli rams grazing in semi-arid environment - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Syed Ali Hassan Naqvi; Alireza Seidavi; Nudrat Aisha Akram; Vito Laudadio; Vincenzo Tufarelli (Tropical Animal Health and Production, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus - Ikram Ullah; Haroon Badshah; Muhammad Imran Naseer; Hae Young Lee; Myeong Ok Kim (NeuroMolecular Medicine, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis, Characterization and Photophysical Properties of Novel Azole Derivatives - Muhammad Saleem; Ki Hwan Lee (Journal of Fluorescence, 2015)

Rhynchophorus ferrugineus midgut cell line to evaluate insecticidal potency of different plant essential oils - Muhammad Rizwan-ul-Haq; Ahmed Mohammed Aljabr (In Vitro Cellular & Developmental Biology - Animal, 2015)

Knowledge, attitude, and practice of Indonesian farmers regarding the use of personal protective equipment against pesticide exposure - Maria G. C. Yuantari; Cornelis A. M. Van Gestel; Nico M. Van Straalen; Budi Widianarko; Henna R. Sunoko; Muhammad N. Shobib (Environmental Monitoring and Assessment, 2015)

Impact of nanoparticles on human and environment: review of toxicity factors, exposures, control strategies, and future prospects - Muhammad Sajid; Muhammad Ilyas; Chanbasha Basheer; Madiha Tariq; Muhammad Daud; Nadeem Baig; Farrukh Shehzad (Environmental Science and Pollution Research, 2015)

Silicon (Si) alleviates cotton (Gossypium hirsutum L.) from zinc (Zn) toxicity stress by limiting Zn uptake and oxidative damage - Shad Ali Anwaar; Shafaqat Ali; Skhawat Ali; Wajid Ishaque; Mujahid Farid; Muhammad Ahsan Farooq; Ullah Najeeb; Farhat Abbas; Muhammad Sharif (Environmental Science and Pollution Research, 2015)

Lipids and proteins—major targets of oxidative modifications in abiotic stressed plants - Naser A. Anjum; Adriano Sofo; Antonio Scopa; Aryadeep Roychoudhury; Sarvajeet S. Gill; Muhammad Iqbal; Alexander S. Lukatkin; Eduarda Pereira; Armando C. Duarte; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

Mass burden and estimated flux of heavy metals in Pakistan coast: sedimentary pollution and eco-toxicological concerns - Usman Ali; Riffat Naseem Malik; Jabir Hussain Syed; Ch. Tahir Mehmood; Laura Sánchez-García; Azeem Khalid; Muhammad Jamshed Iqbal Chaudhry (Environmental Science and Pollution Research, 2015)

Do coal consumption and industrial development increase environmental degradation in China and India? - Muhammad Shahbaz; Sahbi Farhani; Ilhan Ozturk (Environmental Science and Pollution Research, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Bacterial Rhizosphere and Endosphere Populations Associated with Grasses and Trees to be Used for Phytoremediation of Crude Oil Contaminated Soil - Kaneez Fatima; Muhammad Afzal; Asma Imran; Qaiser M. Khan (Bulletin of Environmental Contamination and Toxicology, 2015)

Physiological and biochemical markers to optimize sugar mill wastewater for irrigation in maize (Zea mays L.) crop - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Abida Parveen; Rizwan Alam; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Microbial biotechnology for decolorization of textile wastewaters - Muhammad Imran; David E. Crowley; Azeem Khalid; Sabir Hussain; Muhammad Waseem Mumtaz; Muhammad Arshad (Reviews in Environmental Science and Bio/Technology, 2015)

Resilience of Penicillium resedanum LK6 and exogenous gibberellin in improving Capsicum annuum growth under abiotic stresses - Abdul Latif Khan; Muhammad Waqas; In-Jung Lee (Journal of Plant Research, 2015)

Identification of Mycoplasma suis MSG1 interaction proteins on porcine erythrocytes - Yaning Zhang; Yao Zou; Peipei Ma; Hassan Mushtaq Muhammad; Yufeng Li; Ping Jiang (Archives of Microbiology, 2015)

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Isolation and characterization of pyrroline-5-carboxylate synthetase gene from perennial ryegrass (Lolium perenne L.) - Li Cao; Lei Han; Hua-li Zhang; Hai-bo Xin; Muhammad Imtiaz; Ming-Fang Yi; Zhen-Yuan Sun; Guan-Sheng Ju; Yong-Qiang Qian; Jun-Xiang Liu (Acta Physiologiae Plantarum, 2015)

Living roots magnify the response of soil organic carbon decomposition to temperature in temperate grassland - Paul W. Hill; Mark H. Garnett; John Farrar; Zafar Iqbal; Muhammad Khalid; Nawaf Soleman; Davey L. Jones (Global Change Biology, 2015)
Increasing atmospheric carbon dioxide ( CO 2 ) concentration is both a strong driver of primary productivity and widely believed to be the principal cause of recent increases in global temperature. Soils are the largest store of the world's terrestrial C. Consequently, many investigations have attempted to mechanistically understand how microbial mineralisation of soil organic carbon ( SOC ) to CO 2 will be affected by projected increases in temperature. Most have attempted this in the absence of plants as the flux of CO 2 from root and rhizomicrobial respiration in intact plant‐soil systems confounds interpretation of measurements. We compared the effect of a small increase in temperature on respiration from soils without recent plant C with the effect on intact grass swards. We found that for 48 weeks, before acclimation occurred, an experimental 3 °C increase in sward temperature gave rise to a 50% increase in below ground respiration (ca. 0.4 kg C m −2 ; Q 10 = 3.5), whereas mineralisation of older SOC without plants increased with a Q 10 of only 1.7 when subject to increases in ambient soil temperature. Subsequent 14 C dating of respired CO 2 indicated that the presence of plants in swards more than doubled the effect of warming on the rate of mineralisation of SOC with an estimated mean C age of ca. 8 years or older relative to incubated soils without recent plant inputs. These results not only illustrate the formidable complexity of mechanisms controlling C fluxes in soils but also suggest that the dual biological and physical effects of CO 2 on primary productivity and global temperature have the potential to synergistically increase the mineralisation of existing soil C.

Random mutagenesis and media optimisation for hyperproduction of cellulase from Bacillus species using proximally analysed Saccharum spontaneum in submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Zahid Ali Butt (Natural Product Research, 2015)

Modulatory role of Acacia honey from north-west Nigeria on sodium arsenite-induced clastogenicity and oxidative stress in male Wistar rats - Aliyu Muhammad; Oyeronke A. Odunola; Michael A. Gbadegesin; Ayodeji M. Adegoke; J. Olorunjuwon Olugbami; Ndidi S. Uche (Natural Product Research, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Bioactive constituents from Croton sparsiflorus Morong - Durre Shahwar; Naeem Ahmad; Asma Yasmeen; Muhammad Akmal Khan; Sami Ullah; Rahman Atta-ur (Natural Product Research, 2015)

Recent Advancements in the Treatment of Municipal Wastewater Reverse Osmosis Concentrate—An Overview - Muhammad Umar; Felicity Roddick; Linhua Fan (Critical Reviews in Environmental Science and Technology, 2015)

Seroprevalence of Mycobacterium avium subspecies paratuberculosis (MAP) and evaluation of risk factors in camels of the Sultanate of Oman - Muhammad Hammad Hussain; Muhammad Saqib; Mahir Gharib Al-Maawali; Salim Al-Makhladi; Mohammed Somar Al-Zadjali; Talal Al-Sidairi; Saud Asubaihi; Abdulmajeed Al-Rawahi; Muhammad Khalid Mansoor (Tropical Animal Health and Production, 2015)

Tissue engineering of articular cartilage: From bench to bed-side - Rozlin Abdul Rahman; Muhammad Aa’zamuddin Ahmad Radzi; Norhamiza Mohamad Sukri; Noorhidayah Md Nazir; Munirah Sha’ban (Tissue Engineering and Regenerative Medicine, 2015)

Contribution of greenhouse gas emissions during cropping and fallow seasons on total global warming potential in mono-rice paddy soils - Md. Mozammel Haque; Sang Yoon Kim; Muhammad Aslam Ali; Pil Joo Kim (Plant and Soil, 2015)

Somatic embryogenesis and Agrobacterium-mediated transformation of Gladiolus hybridus cv. ‘Advance Red’ - Jian Wu; Chen Liu; Shanshan Seng; Muhammad Ali Khan; Juanjuan Sui; Benhe Gong; Chao Liu; Chenyu Wu; Xionghui Zhong; Junna He; Mingfang Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

α-Glucosidase inhibitor compounds from Aspergillus terreus RCC1 and their antioxidant activity - Rizna Triana Dewi; Sanro Tachibana; Sofa Fajriah; Muhammad Hanafi (Medicinal Chemistry Research, 2015)

QTL mapping for economically important traits of common carp (Cyprinus carpio L.) - Muhammad Younis Laghari; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Naeem Tariq Narejo; Baoping Xin; Yan Zhang; Xiaowen Sun (Journal of Applied Genetics, 2015)

Effects of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) treatment on ovarian development of the sapphire devil, Chrysiptera cyanea - Muhammad Badruzzaman; Satoshi Imamura; Yuki Takeuchi; Taro Ikegami; Akihiro Takemura (Fish Physiology and Biochemistry, 2015)

Estimating farmers’ willingness to pay for climate change adaptation: the case of the Malaysian agricultural sector - Muhammad Mehedi Masud; Ha Junsheng; Rulia Akhtar; Abul Quasem Al-Amin; Fatimah Binti Kari (Environmental Monitoring and Assessment, 2015)

Removal of Cd, Cr, and Pb from aqueous solution by unmodified and modified agricultural wastes - Muhammad Mahmood-ul-Hassan; Vishandas Suthor; Ejaz Rafique; Muhammad Yasin (Environmental Monitoring and Assessment, 2015)

Impact of marble industry effluents on water and sediment quality of Barandu River in Buner District, Pakistan - Shahi Mulk; Azizullah Azizullah; Abdul Latif Korai; Muhammad Nasir Khan Khattak (Environmental Monitoring and Assessment, 2015)

Diazotrophs-assisted phytoremediation of heavy metals: a novel approach - Abid Ullah; Hafsa Mushtaq; Hazrat Ali; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Hydrogen sulfide alleviates the aluminum-induced changes in Brassica napus as revealed by physiochemical and ultrastructural study of plant - Basharat Ali; Ping Qian; Rui Sun; Muhammad A. Farooq; Rafaqat A. Gill; Jian Wang; Muhammad Azam; Weijun Zhou (Environmental Science and Pollution Research, 2015)

Observed damages in Pakistan due to 16 April 2013 Iran earthquake - Muhammad Masood Rafi; Sarosh H. Lodi; Muhammad Ahmed; Naveed Alam (Bulletin of Earthquake Engineering, 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

Variations of growth, nitrogen accumulation and nitrogen use efficiency among 18 willow clones under two nitrogen regimes - Weidong Yang; Zhiqiang Zhu; Fengliang Zhao; Zheli Ding; Muhammad Tariq Rafiq; Yuyan Wang; Xincheng Zhang; Xiaoe Yang (Agroforestry Systems, 2015)

Characterization of D-genome diversity for tolerance to boron toxicity in synthetic hexaploid wheat and in silico analysis of candidate genes - Muhammad Ilyas; Tariq Mahmood; Ahmad Ali; Muhammad Babar; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2015)

Effects of 2,4-dichlorophenoxyacetic acid combined to 6-Benzylaminopurine on callus induction, total phenolic and ascorbic acid production, and antioxidant activities in leaf tissue cultures of Crataegus azarolus L. var. aronia - Ghaya Chaâbani; Jessica Tabart; Claire Kevers; Jacques Dommes; Muhammad Ishfaq Khan; Sonia Zaoui; Lotfi Chebchoub; Mokhtar Lachaâl; Najoua Karray-Bouraoui (Acta Physiologiae Plantarum, 2015)

Silicon-induced alleviation of NaCl toxicity in okra (Abelmoschus esculentus) is associated with enhanced photosynthesis, osmoprotectants and antioxidant metabolism - Tahira Abbas; Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Aslam Pervez; Chaudhary Muhammad Ayyub; Muhammad Anjum Aqueel; Muhammad Mansoor Javaid (Acta Physiologiae Plantarum, 2015)

A Numerical Study of Effects of Valley-Weathering and Valley-Shape-Ratio on the Ground Motion Characteristics - Jay P. Narayan; Muhammad Y. Arafat; Kamal (Acta Geophysica, 2015)

Protein–Energy Malnutrition: A Risk Factor for Various Ailments - Rizwana Batool; Masood Sadiq Butt; Muhammad Tauseef Sultan; Farhan Saeed; Rabia Naz (Critical Reviews in Food Science and Nutrition, 2015)

Effect of alkaline pretreatment on delignification of wheat straw - Umar Asghar; Muhammad Irfan; Mehvish Iram; Zile Huma; Rubina Nelofer; Muhammad Nadeem; Quratulain Syed (Natural Product Research, 2015)

Effect of Thermal Treatment on Meat Proteins with Special Reference to Heterocyclic Aromatic Amines (HAAs) - Muhammad Asim Shabbir; Ali Raza; Faqir Muhammad Anjum; Moazzam Rafiq Khan; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2015)

Onion: Nature Protection Against Physiological Threats - Hafiz Ansar Rasul Suleria; Masood Sadiq Butt; Faqir Muhammad Anjum; Farhan Saeed; Nauman Khalid (Critical Reviews in Food Science and Nutrition, 2015)

Biocontrol of Fusarium wilt disease in tomato by Paenibacillus ehimensis KWN38 - Kyaw Wai Naing; Xuan Hoa Nguyen; Muhammad Anees; Yong Seong Lee; Yong Cheol Kim; Sang Jun Kim; Myung Hee Kim; Yong Hwan Kim; Kil Yong Kim (World Journal of Microbiology and Biotechnology, 2015)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Changes in the variability and periodicity of precipitation in Scotland - Muhammad Afzal; Alexandre S. Gagnon; Martin G. Mansell (Theoretical and Applied Climatology, 2015)

Seleniferous soils as a source for production of selenium-enriched foods and potential of bacteria to enhance plant selenium uptake - Muhammad Yasin; Ali F. El Mehdawi; Courtney E. Jahn; Aneela Anwar; Marie F. S. Turner; Muhammad Faisal; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2015)

Synthesis, docking studies, and in silico ADMET predictions of some new derivatives of pyrimidine as potential KSP inhibitors - Umer Rashid; Syed Fahad Hassan; Samina Nazir; Abdul Wadood; Muhammad Waseem; Farzana Latif Ansari (Medicinal Chemistry Research, 2015)

POM analyses of anti-kinase activity of thirteen peptide alkaloids extracted from Zizyphus species - Moulay H. Youssoufi; Taibi Ben Hadda; Ismail Warad; Muhammad Moazzam Naseer; Yahia Nasser Mabkhot; Ammar Bader (Medicinal Chemistry Research, 2015)

Evaluation of PAH contamination in soil treated with solid by-products from shale pyrolysis - Jaqueline Nicolini; Muhammad Y. Khan; M. Matsui; Lílian C. Côcco; Carlos I. Yamamoto; Wilson A. Lopes; Jailson B. de Andrade; Clenio N. Pillon; Gregorio G. Carbajal Arizaga; Antonio S. Mangrich (Environmental Monitoring and Assessment, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Assessment of groundwater vulnerability to anthropogenic pollution and seawater intrusion in a small tropical island using index-based methods - Nura Umar Kura; Mohammad Firuz Ramli; Shaharin Ibrahim; Wan Nor Azmin Sulaiman; Ahmad Zaharin Aris; Adamu Idris Tanko; Muhammad Amar Zaudi (Environmental Science and Pollution Research, 2015)

Co-exposure of arsenic and cadmium through drinking water and tobacco smoking: Risk assessment on kidney dysfunction - Muhammad B. Arain; Tasneem G. Kazi; Jameel Ahmed Baig; Hassan I. Afridi; Sarajuddin; Kapil D. Brehman; Haleem Panhwar; Sadaf S. Arain (Environmental Science and Pollution Research, 2015)

In contrast to many other mammals, cetaceans have relatively small hippocampi that appear to lack adult neurogenesis - Nina Patzke; Muhammad A. Spocter; Karl Æ. Karlsson; Mads F. Bertelsen; Mark Haagensen; Richard Chawana; Sonja Streicher; Consolate Kaswera; Emmanuel Gilissen; Abdulaziz N. Alagaili; Osama B. Mohammed; Roger L. Reep; et al. (Brain Structure and Function, 2015)

Variability of aerosol optical depth over Swat in Northern Pakistan based on satellite data - Khan Alam; Rehana Khan; Shahid Ali; Muhammad Ajmal; Gulzar Khan; Wazir Muhammad; Malak Azmat Ali (Arabian Journal of Geosciences, 2015)

Geochemical study of the Cretaceous–Tertiary boundary succession exposed at Duhok Dam area (eastern Tethys): Northern Iraq - Muhammad S. Salih; Majid M. Al-Mutwali; Salim M. Aldabbagh (Arabian Journal of Geosciences, 2015)

Cd, Ni, and Pb distribution and pollution assessment in roadside dust from Baghdad City and Western Iraqi Desert - Salih Muhammad Awadh (Arabian Journal of Geosciences, 2015)

Rhodococcus biphenylivorans sp. nov., a polychlorinated biphenyl-degrading bacterium - Xiaomei Su; Yindong Liu; Muhammad Zaffar Hashmi; Jinxing Hu; Linxian Ding; Min Wu; Chaofeng Shen (Antonie van Leeuwenhoek, 2015)

Genetic diversity revealed by physiological behavior of citrus genotypes subjected to salt stress - Sajjad Hussain; Raphaël Morillon; Muhammad Akbar Anjum; Patrick Ollitrault; Gilles Costantino; François Luro (Acta Physiologiae Plantarum, 2015)

Anthocyanin production in the hyperaccumulator plant Noccaea caerulescens in response to herbivory and zinc stress - Saeed Ahmad Asad; Said Muhammad; Muhammad Farooq; Aftab Afzal; Martin Broadley; Scott Young; Helen West (Acta Physiologiae Plantarum, 2015)